Penerapan Strategi Contextual Teaching and Learning untuk Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Fikih di MTs. Al-Ikhlas Mentigi - Haulid Haulid (Jurnal Paedagogy, 2021)
This study aims to describe the increase in student learning activity through the application of CTL (contextual teaching and learning) strategies. This research method uses classroom action research which is carried out in 2 cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The subjects of this study were 27 MTs class VII students. Al-Ikhlas Mentigi. The research instrument uses observation and tests, while the data analysis technique uses qualitative and quantitative descriptive analysis. The results of this study indicate that the application of the CTL (contextual teaching and learning) strategy is proven to increase learning activity which has an impact on student learning outcomes in Fiqh subjects. In addition, students feel happy about this learning strategy, this is manifested by the growing sense of togetherness in the group, the class atmosphere becomes more lively and there is a new experience for students to conduct a simple analysis of a problem that arises around them.